A Novel Microcrystalline BAY-876 Formulation Achieves Long-Acting Antitumor Activity Against Aerobic Glycolysis and Proliferation of Hepatocellular Carcinoma - Yang, Hua; Zhang, Mu-Zi-he; Sun, Hui-wei; Chai, Yan-tao; Li, Xiaojuan; Jiang, Qiyu; Hou, Jun (Frontiers in Oncology, 2021)
BAY-876 is an effective antagonist of the Glucose transporter type 1 (GLUT1) receptor, a mediator of aerobic glycolysis, a biological process considered a hallmark of hepatocellular carcinoma (HCC) together with cell proliferation, drug-resistance, and metastasis. However, the clinical application of BAY-876 has faced many challenges. In the presence study, we describe the preparation of a novel microcrystalline BAY-876 preparation. A series of HCC tumor models were established to determine not only the sustained release of microcrystalline BAY-876, but also its long-acting antitumor activity. The clinical role of BAY-876 was confirmed by the increased expression of GLUT1, which was associated with the worse prognosis among advanced HCC patients. A single dose of injection of microcrystalline BAY-876 directly in the HCC tissue achieved sustained localized levels of Bay-876. Moreover, the single injection of microcrystalline BAY-876 in HCC tissues not only inhibited glucose uptake and prolonged proliferation of HCC cells, but also inhibited the expression of epithelial-mesenchymal transition (EMT)-related factors. Thus, the microcrystalline BAY-876 described in this study can directly achieve promising localized effects, given its limited diffusion to other tissues, thereby reducing the occurrence of potential side effects, and providing an additional option for advanced HCC treatment.